Monitoring Human Rights: The Experience of the UPR Brazil Coalition - Lapa, Fernanda; Zimermann Bail, Suiany (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2022)
This article explores the creation of the UPR Brazil Coalition, a civil society network that monitors human rights using the Universal Periodic Review (UPR), a United Nations mechanism. It first presents the importance of social participation for the rule of law and for the Brazilian democratic legal system. In then introduces the UPR mechanism, including its creation in 2006, the basic aspects of its operation, and the three Brazilian review cycles. The article then discusses Brazilian civil society’s engagement with the UPR and the creation and current activities of the UPR Brazil Coalition, the main network that monitors the human rights situation in Brazil by means of evaluating implementation of UPR recommendations.